Translation and TS research in a culture using a language of limited diffusion: the case of Slovenia - Pokorn, Nike K. (The Journal of Specialised Translation, 2008)
The article presents the seminal influence of translation on the development of Slovene language and culture. A historical overview of major translations in Slovene demonstrates the decisive influence of translation on the development of Slovene language, prose, drama, and poetry. The present state of interlingual exchange in Slovenia is briefly presented, in which translated literatures in certain genres represent more than a half of yearly publications. The article also focuses on another typical feature of Slovene culture that is shared by many other cultures using a language of limited diffusion: Slovene translators predominantly translate out of their native language if they want to meet the demands of the market. The article concludes with a brief overview of the main currents in Slovene TS research and ends with a plea, first launched by Koskinen in 2007, for a new direction in research that would be more explicitly oriented towards the needs of professionals and the general public.